2016
DOI: 10.1097/qad.0000000000001283
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol

Abstract: Objective:To investigate the toxicity and activity against HIV of 5-hydroxytyrosol as a potential microbicide.Design:The anti-HIV-1 activity of 5-hydroxytyrosol, a polyphenolic compound, was tested against wild-type HIV-1 and viral clones resistant to nucleoside reverse transcriptase inhibitors (NRTIs), non-nucleoside reverse transcriptase inhibitors (NNRTIs), protease inhibitors and integrase inhibitors. In addition to its activity against founder viruses, different viral subtypes and potential synergy with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…HTyr was identified as a unique class of HIV-1 inhibitors that prevent HIV from entering into the host cell and binding the catalytic site of the HIV-1, with both, viral entry and integration inhibited [91]. Furthermore, it was reported that HTyr inactivated influenza A viruses, suggesting that the mechanism of the antiviral effect of HTyr might require the presence of a viral envelope [92].…”
Section: Hydroxytyrosolmentioning
confidence: 99%
“…HTyr was identified as a unique class of HIV-1 inhibitors that prevent HIV from entering into the host cell and binding the catalytic site of the HIV-1, with both, viral entry and integration inhibited [91]. Furthermore, it was reported that HTyr inactivated influenza A viruses, suggesting that the mechanism of the antiviral effect of HTyr might require the presence of a viral envelope [92].…”
Section: Hydroxytyrosolmentioning
confidence: 99%
“…MT-2 cells is an established cell line of CD4+ T cells, easier to manipulate and obtain than primary human cells, thus suitable for first line studies of anti-HIV effect and, therefore broadly used to test the efficacy experimental antiviral agents thanks to its high reproducibility. [50][51][52] HIV-1 exerts a profound cytopathic (CPE) effect against CD4+ T lymphocytes. Once infected, the lymphocytes accumulate viral DNA and actively produce HIV proteins, which results in the concomitant lysis of such infected cells by apoptosis.…”
Section: Hiv-antiviral Activity Of Catazt-ncpsmentioning
confidence: 99%
“…Hydroxytyrosol antiviral mechanisms were showed through its inactivation effects on influenza A viruses, especially during the virus morphological changes, such as the presence of a viral envelope which is an integral membrane protein involved in several aspects of the virus life cycle including its assembly, budding, and pathogenesis [72]. The mechanisms of which OO nutraceuticals protect against viral infections have often focused on the hydroxytyrosol preventative effects on HIV from entering the host cell and binding the catalytic site of the HIV-1, and its inhibitory effect on both viral entry and integration [73]. Regular intake of olive leaf extracts, rich in polyphenol flavonoids, have been shown to be responsible for a 33% reduction in URI [74].…”
Section: Potential Antiviral Benefits Of Olive Oil Nutraceuticalsmentioning
confidence: 99%